2020
DOI: 10.1093/jme/tjaa130
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Occurrence of Amblyomma maculatum sensu lato (Acari: Ixodidae) and Rickettsia parkeri (Rickettsiales: Rickettsiaceae), Arizona and New Mexico, 2017–2019

Abstract: Abstract Amblyomma maculatum Koch sensu lato (s.l.) ticks are the vector of Rickettsia parkeri in Arizona, where nine cases of R. parkeri rickettsiosis have been identified since the initial case in 2014. The current study sought to better define the geographic ranges of the vector and pathogen and to assess the potential public health risk posed by R. parkeri in this region of the southwestern United States. A total of 275 A. maculatum s.l. ticks were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…While R. parkeri has been reported in New Mexico from A. maculatum sensu lato, this is the first report of R. parkeri from Dermacentor spp . in New Mexico [20]. Rickettsia parkeri Black Gap was characterized from a D. parumapertus tick isolate collected in Brewster County, Texas in 2015 and closely related bacteria have been identified in the same tick species from Utah and Arizona in the Western United States and the states of Sonora and Chihuahua in Northern Mexico [48, 49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While R. parkeri has been reported in New Mexico from A. maculatum sensu lato, this is the first report of R. parkeri from Dermacentor spp . in New Mexico [20]. Rickettsia parkeri Black Gap was characterized from a D. parumapertus tick isolate collected in Brewster County, Texas in 2015 and closely related bacteria have been identified in the same tick species from Utah and Arizona in the Western United States and the states of Sonora and Chihuahua in Northern Mexico [48, 49].…”
Section: Discussionmentioning
confidence: 99%
“…Collection sites ( Fig 1 ) were chosen based on accessibility and encompassed a range of elevation and habitat. We included one location in southwestern NM where A. maculatum had previously been collected [20]. Study areas ranged in elevation from 1,000 m to 2,810 m.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary vectors of R. parkeri in North America are the ixodid ticks Amblyomma maculatum Koch sensu stricto (s. s.) in the eastern and Gulf Coast regions of the United States and A. maculatum sensu lato (s. l.) in southern Arizona ( 10 12 , 14 , 15 ). Recent field studies further identified R. parkeri sensu stricto (s. s.) in A. maculatum s. l. ticks in West Texas ( 16 ) and New Mexico ( 17 ), as well as in the northern state of Sonora ( 18 ) and the southeastern state of Tabasco, Mexico ( 19 ). In South America, Amblyomma triste Koch and Amblyomma tigrinum Koch, both members of the Amblyomma maculatum tick group ( 20 ), are the primary vectors of R. parkeri s. s. ( 5 , 6 , 21 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…3,[6][7][8] Since then, additional cases of R. parkeri rickettsiosis have been reported in many southeastern and southwestern regions of the United States. [9][10][11] In addition to the primary vector, A. maculatum, R. parkeri has also been found in different species of ticks, including Amblyomma americanum, [12][13][14] Amblyomma triste, 15 and Ixodes scapularis. 14,16 R. amblyommatis, formerly named Rickettsia amblyommii and 'Candidatus Rickettsia amblyommii', has been detected in A. americanum throughout the United States.…”
Section: Introductionmentioning
confidence: 99%